„Unreliable“ 50th Lithuanian rifle division - Pocius, Mindaugas (Genocidas ir rezistencija, 1998)
In the summer of 1944, the red army invaded Lithuania. Forced mobilisation into the army of the new occupier began soon after. Mobilising Lithuanian men to join the USSR was particularly difficult for the Bolsheviks. Thousands of young men hid from conscription in villages and forests, joining partisan groups instead. The NKVD punitive regiments managed to catch some of those in hiding and thus increase the ranks of potential death squads. However, the ‘conscripts’ who arrived at the commissariats or were forcibly captured were not immediately sent to the front – they had to undergo ‘training’ in reserve regiments.